Quantifying compliance and acceptance through public and private social conformity - Sowden, Sophie; Koletsi, Sofia; Lymberopoulos, Eva; Militaru, Elisabeta; Catmur, Caroline; Bird, Geoffrey (Consciousness and cognition, 2018)
•Most measures of social conformity conflate compliance and acceptance.•Compliance occurs when individuals conform in public, but not in private.•Acceptance occurs when group influence is internalised, in private and in public.•Our task reveals the presence of compliance and acceptance on a within-subject basis.•The magnitude of compliance increases as the size of the majority increases. Social conformity is a class of social influence whereby exposure to the attitudes and beliefs of a group causes an individual to alter their own attitudes and beliefs towards those of the group. Compliance and acceptance are varieties of social influence distinguished on the basis of the attitude change brought about. Compliance involves public, but not private conformity, while acceptance occurs when group norms are internalised and conformity is demonstrated both in public and in private. Most contemporary paradigms measuring conformity conflate compliance and acceptance, while the few studies to have addressed this issue have done so using between-subjects designs, decreasing their sensitivity. Here we present a novel task which measures compliance and acceptance on a within-subjects basis. Data from a small sample reveal that compliance and acceptance can co-occur, that compliance is increased with an increasing majority, and demonstrate the usefulness of the task for future studies of conformity.